Deriving the Kramers’ dispersion formula from the canonical transformations of Heisenberg’s equation of motion - Yong-Yi Huang (Results in Physics, 2024)
We obtain the canonical transformations for the time-dependent Hamiltonian from Heisenberg’s equation of motion, based on which we derive the Kramers’ dispersion formula via the perturbation theory of matrix mechanics to the second order approximation.